Unusual titanium-induced McMurry coupling of 4-oxo-4H-chromene-2-carbaldehydes enroute to bis-chromones. (24th February 2021) - Yerrabelly, Jayaprakash Rao; Bathini, Pavan Kumar; Yerrabelly, Hemasri; Vadapalli, Kishore
Abstract : Ti/Zn-mediated McMurry coupling of a series of 4-oxo-4 H -chromene-2-carbaldehydes afforded unusual chemoselective CH2 –CH2 tethered bis-chromones. Abstract : Ti/Zn-mediated McMurry coupling of a series of 4-oxo-4 H -chromene-2-carbaldehydes afforded unusual chemoselective CH2 –CH2 tethered bis-chromones. Studying the reaction parameters and reagents further confirmed that the formation of unexpected coupled products is selective to 4-oxo-4 H -chromene-2-carbaldehydes. This methodology demonstrated a simple and efficient route for the synthesis of bis-chromones.